(Vapour + liquid) equilibria of (fluoromethane + tetrafluoromethane) at the temperature 130.46 K - Fonseca, I. M. A. (1998)
The total vapour pressure of binary liquid mixtures of (fluoromethane+tetrafluoromethane) has been measured at the temperature 130.46 K. Two partially miscible liquid phases were found. The excess molar Gibbs energy was calculated in the region where the two liquids are mutually soluble. For the hypothetical equimolar mixture,GEm01 (x=0.5)=846 J<@TBLEND>mol-1.